PERAN ORGANISASI DAN KOMPONEN KURIKULUM DALAM MEWUJUDKAN PEMBELAJARAN BERPUSAT PADA SISWA - Siti Nur Azizah; Mutia Rohman; Fani Alifya Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In order to understand student centered learning, this study looks at the significance of curriculum organization and its parts. The issue found is that learning in Indonesia is still teacher centered, which leads to poor student engagement. The goal of this study is to examine how the curriculum structure and its components, such as goals, content, methods, and assessment, promote student centered learning. Using a literature review technique, this study takes a qualitative approach by examining journals, books, and prior research. The results show that curriculum organizations such as separated curriculum, correlated curriculum, broadfields curriculum, and integrated curriculum support active learning. Curriculum components also play important roles in increasing student activeness. Clear objectives develop critical thinking skills, relevant content improves learning motivation, and student centered methods such as project based learning encourage active knowledge construction. Process oriented evaluation also provides comprehensive feedback on student learning development. However, student centered learning still faces obstacles such as dense curricula, limited teacher understanding, inadequate facilities, and changing educational policies. Therefore, well designed curriculum organization and integrated curriculum components are essential in creating effective, innovative, and student centered learning.